Influence of nitrogen fertilization on yield and phenolic compounds in wheat grains (Triticum aestivum L. ssp. aestivum). Issue 1 (30th November 2018) - Stumpf, Beate; Yan, Feng; Honermeier, Bernd
Abstract: Nitrogen (N) is an important plant nutrient and is crucial for the plant growth and grain yield formation of field crops such as wheat ( Triticum aestivum L. ssp. aestivum ). However, little is known about the influence of N on secondary metabolites in wheat grains which are supposed to be beneficial for human health due to their antioxidant potentials. Therefore, we investigated the influence of N fertilization on plant growth and yield performance of winter wheat, as well as on total phenolic concentration, antioxidant capacity, and the accumulation of (in)soluble phenolic acids in wheat grains during the grain‐filling phase. It was found that ferulic acid was the predominant phenolic acid in wheat grains. As expected, higher amounts of N fertilizer led to increasing grain yields, whereas the concentration of soluble ferulic acid decreased. In contrast, insoluble bound ferulic acid, total phenolic content, and antioxidant capacity were not affected by the N treatment. Insoluble phenolic compounds seemed to be less susceptible to variations in N supply.